GAMBARAN TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN INFORMASI OBAT DI APOTEK RAWAT JALAN RSUD LABUANG BAJI MAKASSAR - Isya Syamsu, A. Suparlan; Farida, Farida (Fakultas Farmasi UMI, 2015)
The research is conducted to determine the satisfaction level of patients of drug information service at pharmacy of Makassar Labuang Baji Hospital. This research used descriptive method using primary data by distributing questionnaires filled by the respondents. Data was collected by distributing questionnaires to 42 respondents who were outpatients. The questionnaire has five dimensions they are responsiveness, accurance / guarantee or assurance, empathy, reliability, tangible. Each dimension has three questions regarding drug information service conducted pharmacists in Makassar Labuang Baji Hospital. The research result is the highest patient satisfaction with the drug information service is the responsiveness and empathy dimension concern with the gained of the patient (98 %) and the lowest patient satisfaction with the drug information service is the Reability / reliability dimension with the gained of 86%. Based on the questionnaire result can be concluded that the level of patient satisfaction with the drug information service in pharmacies of Makassar Labuang baji Hospital is largely satisfied as much as 96.4%. It is hoped Makassar Labuang Baji Hospital to retain and keep improving the quality of drug information services so it can be an example for other hospitals as well.